Comparative planetary circulation regimes in simple general circulation models - Wang, Y (2014)
This thesis presents the studies of terrestrial planetary atmospheric circula- tion regimes using simplified GCMs with different levels of complexity. Two different versions of the simplified GCM PUMA (Portable University Model for the Atmosphere) are used — PUMA-S with Newtonian cooling scheme and PUMA-G with a semi-grey two-band radiative transfer scheme and dry convective adjustment. A series of controlled experiments are conducted by varying planetary rotation rate and imposed equator-to-pole temperature difference using PUMAS-S, and by varying rotation rate, planetary obliquity, and the ratio of optical depth in long-wave (thermal radiation) band to that in short-wave (stellar radiation) band using PUMA-G. These defining parameters are further combined with each other into dimensionless forms to establish parameter spaces, in which the occurences of different circulation regimes are mapped and classified. For the PUMA-S experiments, very coherent trends when varying planetary rotation rate (thermal Rossby number) is found. It is demonstrated that the GRW mechanism is mainly responsible for the equatorial super-rotation observed in our experiments. Regular baroclinic waves are obtained at intermediate values of thermal Rossby number and depend strongly on the strength of radiative and frictional damping. Global atmospheric energetics in terms of Lorenz energy cycle and meridional heat transport efficiency also exhibits strong dependence on planetary rotation rate from our PUMA-S experiments. Theories of geostrophic turbulence (especially the recently introduced zonostrophic turbulence) and jet formation are examined using the PUMA-S experiments. For the PUMA-G experiments, Similar trends are observed with respect to varying planetary rotation rate, while new regimes like strongly subrotating atmospheres are found when varying obliquity in PUMA- G. Tidally-locked planets are also studied by modifying the incoming stellar irradiation in PUMA-G. It is found that atmospheric optical depth in the longwave band plays an important role in setting the heat transport efficiency from day-side to night-side. These results provide significant insights into the terrestrial planetary atmospheric circulation dynamics and the inference of circulation regimes of extrasolar planets. Future studies will focus on the effect of seasonal/diurnal cycle, the parametrisation of eddy heat transport efficiency, as well as the modification of the two-band semi-grey radiative transfer scheme to incorporate pressure broadening effects.